Improving Vocabulary Achievement of Young Learners Using Animated Video - S Syarifudin; M Muhammad (International Journal on Advanced Science, Education, and Religion, 2018)
This study aims at finding out whether or not the use of video improves the learners’ vocabulary of the young learners. This study applied pre-experimental method with one group pre-test and post-test design. Twenty junior high school learners in Mataram involved in this study. The data were collected through vocabulary test (pre-test and post-test). This study used cluster random sampling technique. A t-test was used to measure the significance of animated video usage in improving young learners’ vocabulary achievement. Mean score of post-test was greater than the mean score of the pre-test. This study revealed that using animated video can improve learners’ vocabulary of the young learners